A Feminist Perspective on Trauma Studies in the Hebrew Bible: The Unnamed Jephthah’s Daughter (Jdg 11:29–40) - Lidia Rodríguez Fernández (Religions, 2025)
Since the beginning of the 21st century, studies on “cultural trauma” have pushed Hebrew Bible exegesis in new directions. Although its initial focus was on the period of the Babylonian exile (6th century BC), after 25 years of research, this novel framework has shown its fruitfulness when reading a range of literature: poetic and prophetic literature, as well as narratives of sexual violence. Trauma studies also engage an inspiring dialogue with other disciplines that are already well established in biblical exegesis, such as feminist scholarship. The aim of this article is twofold: on the one hand, we will introduce the concept of “cultural trauma” and the main features that characterise the narratives responding to cultural trauma. On the other hand, we will present the main contributions of this frame of reference to recent Hebrew Bible research and the concrete contributions to a text as disturbing as the sacrifice of Jephthah’s daughter in Judges 11:29–40.